Analisis Penerapan Sistem Informasi Manajemen Rumah Sakit Menggunakan Metode UTAUT dan TTF - Novianti Puspitasari; Adhistya Erna Permanasari; Hanung Adi Nugroho (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2013)
Ministry of Health RI has issued a policy to guide the implementation of health development undertaken by the government and private sector in order to improve the quality of health services at the hospital. This quality improvement is formed by the implementation of Hospital Management Information System (HMIS) in every hospital. The implementation of HMIS is still having problems and obstacles in the level of user acceptance. There are still many operational and managerial things that, makes the implementation of HMIS not properly running.This research study analyses the results of the implementation of HMIS from the user acceptance levels, using the integration model of the Task Technology Fit (TTF) and the Unified Theory of Acceptance and Usage of Technology (UTAUT).